2018
DOI: 10.46527/2582-3264.108
|View full text |Cite
|
Sign up to set email alerts
|

Combat Exposure and Peritraumatic Factors Predicting PTSD among Military Personnel Fighting Insurgency in Nigeria

Abstract: Previous studies indicate that posttraumatic stress disorder is one of the major mental health challenges that affect military personnel who have experienced combat situations. However, there is still paucity of research on the factors that predict PTSD in Nigerian military setting despite increasing rate of Boko-Haram exposure. This study therefore examined the predictive influence of peritraumatic factors (combat exposure, number of deployments, duration of deployments and substance use) among Nigerian milit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The subscales have been reported to have a high degree of intercorrelation (r = .87) (Nwoga, Audu, & Obembe, 2016). Similarly, a high level of internal consistency (Intrusion:.87-.94, Avoidance: 84 -.87, Hyperarousal: = .79-.91) has been reported by previous studies (Cuijpers et al, 2020;Abel et al, 2018;Filion, Munroe-Chandler, & Loughead, 2021;Meggs & Mark, 2019;Vrijkotte et al, 2016;Clare et al, 2017;Elliot, 1999;Nicholls, 1984;Adeoya, Adeleye, & Egawa, 2021;Tashman, Simpson, & Cremades, 2018;Weiss & Marmar, 1997;Creamer et al, 2013). The authors reported a test-retest reliability coefficient of .89 to .94 after a 6-month interval (Weiss & Marmar, 1997).…”
Section: Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…The subscales have been reported to have a high degree of intercorrelation (r = .87) (Nwoga, Audu, & Obembe, 2016). Similarly, a high level of internal consistency (Intrusion:.87-.94, Avoidance: 84 -.87, Hyperarousal: = .79-.91) has been reported by previous studies (Cuijpers et al, 2020;Abel et al, 2018;Filion, Munroe-Chandler, & Loughead, 2021;Meggs & Mark, 2019;Vrijkotte et al, 2016;Clare et al, 2017;Elliot, 1999;Nicholls, 1984;Adeoya, Adeleye, & Egawa, 2021;Tashman, Simpson, & Cremades, 2018;Weiss & Marmar, 1997;Creamer et al, 2013). The authors reported a test-retest reliability coefficient of .89 to .94 after a 6-month interval (Weiss & Marmar, 1997).…”
Section: Methodsmentioning
confidence: 58%
“…The results revealed a significant positive relationship between combat exposure, substance use coping, and PTSD. Similarly, Abel et al (2018) investigated the influence of combat exposure on PTSD among military combatants in North Eastern Nigeria using 249 purposely drawn men and officers of the Nigerian Army on operation. They found that combat exposure was significant for avoidance symptoms and re-experiencing symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the African countries that were selected vary in levels and types of trauma exposure distribution. For example, traumatic outcome of a high level of individuals who suffer from HIV (Adewuya et al, 2009), ethnoreligious conflicts (Obilom & Thacher, 2008), and war-related traumas are observed in Nigeria (Abel et al, 2018), whereas violence against women is predominantly observed in Ghana (Issahaku, 2015). Our results show that the cutoff levels are different among the different African countries and from previous findings from Israel.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the magnitude of PTSD in Sub-Saharan Africa have shown estimates ranging from 0% to 74% at national and regional levels, with a combined magnitude of 30% in war-affected areas ( 23 ). In Nigeria, recent research indicates that three out of 10 military combatants are at risk of developing PTSD ( 24 ).…”
Section: Introductionmentioning
confidence: 99%